HUBUNGAN PERUBAHAN RUTINITAS KELUARGA DAN PERILAKU GERAK ANAK DENGAN PERKEMBANGAN ANAK USIA PRASEKOLAH DI WILAYAH RW 14 KELURAHAN JATIRAHAYU - Faradilla Azzahra (2022)
The family environment is one of the factors to determine how the child will develop in the future. Routines in family can support aspects of children's readiness, namely by guiding children's movement behavior that supports early development. The existence of a bad family routine can cause developmental risks in children. This study aims to determine the correlation between changes in family routines and movement behavior of children with the development of preschool age children in RW 14 Jatirahayu Village. The design of this study is quantitative with a cross sectional approach. The sampling technique used proportional random sampling as many as 103 respondents. Analysis of the data used in this study is the Chi-Square test. The results of this study indicate that there is a significant correlation between changes in family routines and child development with p-value = 0,000. And there is a significant correlation between the behavior of children's movements with child development, with p-value = 0.000. This study are expected mothers can apply behavioral regulation and control, as well as the child's developmental screening regularly.